Trinidad Leaseholds Ltd. - (:unkn) unknown (My University, 2010)
The fuel truck or tanker in this vintage photograph is parked on a road with trees in the background. This could be a photograph at the compound of Trinidad Leaseholds Ltd. Fuel trucks are used to transport gasoline to gas stations. The sign at the back of the truck says “Buy Regent Super British Petrol”. Part of the sign on the truck’s cab door is legible and reads “Trinidad Leaseholds Ltd. 43”. Someone is standing alongside the truck near the cab. He is wearing a hat, which is shaped like a pilot’s and a long white coat over a shirt, tie and pants.
Colour: Black and White; Style: Landscape; Other: Bordered; Divided
Keywords: Trinidad and Tobago; Postcards; Petroleum--Transportation; Tankers; Gasoline industry; Clothing and dress; Men; Petroleum workers